2016
DOI: 10.1016/j.cognition.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and long-lasting learning of feature binding

Abstract: How are features integrated (bound) into objects and how can this process be facilitated? Here we investigated the role of rapid perceptual learning in feature binding and its long-lasting effects. By isolating the contributions of individual features from their conjunctions between training and test displays, we demonstrate for the first time that training can rapidly and substantially improve feature binding. Observers trained on a conjunction search task consisting of a rapid display with one target-conjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 54 publications
2
27
1
Order By: Relevance
“…The dependence of transfer on the specific orientation value has implications for the investigation and interpretation of VPL transfer and specificity using oriented stimuli. Indeed such stimuli have been commonly used to investigate VPL, including in orientation discrimination tasks (e.g., [ 25 , 30 , 32 34 ]), visual search (e.g., [ 10 , 30 , 35 , 36 ]) and texture discrimination tasks (e.g., [ 37 41 ]). Some VPL studies have varied orientation values to manipulate task properties, such as task difficulty, and then linked those task properties to the resulting feature specificity (e.g., [ 10 , 30 , 37 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of transfer on the specific orientation value has implications for the investigation and interpretation of VPL transfer and specificity using oriented stimuli. Indeed such stimuli have been commonly used to investigate VPL, including in orientation discrimination tasks (e.g., [ 25 , 30 , 32 34 ]), visual search (e.g., [ 10 , 30 , 35 , 36 ]) and texture discrimination tasks (e.g., [ 37 41 ]). Some VPL studies have varied orientation values to manipulate task properties, such as task difficulty, and then linked those task properties to the resulting feature specificity (e.g., [ 10 , 30 , 37 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, expert radiologists employ efficient search strategies when viewing medical images, such that they are faster and make fewer perceptual errors in discriminating abnormal from healthy tissue compared to novices ( Waite, Grigorian, Alexander, Macknik, Carrasco, Heeger, & Martinez-Conde, 2019 ). Robust learning has generally been thought to require extensive and repeated training ( Frank, Reavis, Tse, & Greenlee, 2014 ; Karni & Sagi, 1993 ; Watanabe, Náñez, Koyama, Mukai, Liederman, & Sasaki, 2002 ; Yotsumoto, Watanabe, & Sasaki, 2008 ), but recent studies have demonstrated long-lasting performance enhancements with short training periods ( Hussain, Sekuler, & Bennett, 2011 ; Yashar & Carrasco, 2016 ; Yashar, Chen, & Carrasco, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it represents enhanced perceptual sensitivity or discriminability regarding the trained stimulus and task demands (for reviews, see Seitz, 2017 ; Watanabe & Sasaki, 2015 ), and thus serves as evidence of neuroplasticity in the adult, and even the elderly (DeLoss, Watanabe, & Andersen, 2015 ) brain. Such performance benefits can be long lasting (Karni & Sagi, 1993 ; Watanabe et al, 2002 ), even with very short training periods (Yashar & Carrasco, 2016 ; Yashar, Chen, & Carrasco, 2015 ).…”
Section: Introductionmentioning
confidence: 99%